Literasi Asuransi Personal Accident di PT. Asuransi Sinar Mas Cabang Solo Pada Mahasiswa Sekolah Vokasi Universitas Sebelas Maret Surakarta - Anisa Fisa Bilhillah; Endang Martini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Insurance literacy among the younger generation is a crucial issue in improving understanding of financial products, including personal accident insurance. This study aims to determine the level of literacy of University Vocational School (UNS) students regarding personal accident insurance products at PT. Asuransi Sinar Mas Solo Branch. This study used qualitative methods with in-depth interviews with randomly selected students and questionnaires distributed to University Vocational School (UNS) students. Data were analyzed to identify understanding, barriers, and opportunities for improving literacy. The results showed that student literacy levels were still varied, with the main obstacles being difficult to understand technical terms, lack of education, and minimal outreach from insurance companies. Some students did not fully understand the benefits and procedures for insurance claims. Based on these findings, it can be concluded that student literacy regarding personal accident insurance still needs to be improved through more active education and outreach programs, including the use of digital technology. Literasi asuransi di kalangan generasi muda menjadi isu penting dalam meningkatkan pemahaman terhadap produk keuangan, termasuk asuransi personal accident. Penelitian ini bertujuan untuk mengetahui sejauh mana tingkat literasi mahasiswa Sekolah Vokasi Universitas (UNS) terhadap produk asuransi personal accident di PT.Asuransi Sinar Mas Cabang Solo. Penelitian ini menggunakan metode kualitatif dengan teknik wawancara mendalam kepada mahasiswa yang dipilih secara acak dan penyebaran kuesioner kepada mahasiswa Sekolah Vokasi Universitas (UNS). Data dianalisis untuk mengidentifikasi pemahaman, hambatan, dan peluang peningkatan literasi. Hasil penelitian menunjukkan bahwa tingkat literasi mahasiswa masih beragam, dengan kendala utama berupa istilah teknis yang sulit dipahami, kurangnya edukasi, serta minimnya sosialisasi dari perusahaan asuransi. Sebagian mahasiswa belum memahami manfaat dan prosedur klaim asuransi dengan baik. Berdasarkan temuan tersebut, dapat disimpulkan bahwa literasi mahasiswa terhadap asuransi personal accident masih perlu ditingkatkan melalui program edukasi dan sosialisasi yang lebih aktif, termasuk pemanfaatan teknologi digital.